Power Quality Enhancement Using Passive Power Filters. Issue 1 (23rd February 2023) - Varshney, Gunjan; Mittal, Udit; Pawar, Abhilasha
Abstract: Harmonics in Power system are dangerous in electrical distribution power systems. Harmonics in the line current promotes instability, losses and also the voltage distortion. Due to properties of power electronics converters, power lines have become highly polluted. The problems of bad power quality are due to higher switching frequencies and the non‐linearity properties of power electronic devices. So, to compensate these problems priority is being given to the development of Power Filters. Both types of filters, i.e., passive and active are often used for harmonics producing load to avoid distortions. Shunt type filters influences the harmonic reduction at medium or high voltage level, whereas active filters have been declared for low or medium voltage ratings. Along distinct applications consisting the reactive power and harmonics compensation, passive filters are found to be suitable. Passive filters have been adopted for harmonic compensation in distribution systems due to low cost, integrity, reliability, and controls less operation. Therefore, to mitigate these harmonics, different topologies of passive filters are designed and their different combined performances in MATLAB/Simulink are evaluated. The filter can compensate harmonic currents, reactive power, and power factor. The simulation results presented in this research show that the proposed approach can provide good dynamic and steady‐state performance.